GENDER DIFFERENCES (PURUSA PRADANA) AND METACOGNITIVE SKILLS IN BALI - Putu Eka Suarmika; Erdi Guna Utama (STKIP Singkawang, 2018)
Balinese culture places women as subordinate because there is a misconception of the concept of purusa and pradana. Indeed purusa and pradana exist in every man including also in women. Purusa is the soul and pradana is the body.Basically, gender issues are not just about the problems of male and female relationships, but also with the issue of education. The purpose of this study was to determine the effect of gender differences (purusa and pradana) on the metacognitive skills of grade 5 primary school students. The survey design used was cross sectional survey design, the researchers collected data at a single point of time. The data collected were metacognitive skill data of grade 5 primary school students. Based on the results of empirical analysis, there is no significant difference between men and women on metacognitive skills with sig 0.672> 0.05. Metacognitive, especially skill is not something to be gained but needs to be trained in learning both in school, family and society. This means that to form students who have high metacognitive skills need cooperation between the school as a formal executive education with school committees (parents of students) by utilizing various sources that exist in the student environment are located.